Accidents Among Drillers in the Venezuelan Oil Industry in 1993. - Fernández-DÂ´Pool, Janice; D í¶ í¶s, Marianne (Investigación Clínica, 2009)
In 1993 a total of 356 accidents with injuries occurred in workers of 26 companies of oil and gas extraction in the eastern coast of Maracaibo Lake in Venezuela. 288 of them worked in drilling tasks. With the purpose of analyzing the factors that are associated with the drilling activities, the data base of the Venezuela Institute of Social Security, was reviewed. Only the first two digits of the Standard Industrial Classification were used in this study. For preventive reasons this study focused on six variables: unsafe condition or mechanical cause, insecure action, external agent, type of the accident, part of the body injured and the nature of the injury. The following results were obtained: the frequency rate was 222.3 by 1,000, most of them were minor and were caused by not paying attention when walking on or around labor areas (37%), thus favoring being struck by lifting machines (14%); also 62% occurred in non-classified conditions that injured the upper and lower extremities (48% and 24%) producing contusions and crushing (39%). In conclusion, most injuries occurring in the activity of oil and gas extraction are due to factors controllable with preventive strategies